Washout Duration of Prostaglandin Analogues: A Systematic Review and Meta-analysis - Vlad Diaconita; Matthew Quinn; Dania Jamal; Brad Dishan; Monali S. Malvankar-Mehta; Cindy Hutnik (Journal of Ophthalmology)
Topic. Prostaglandin analogues (PGAs) are first-line medical therapy for primary open angle glaucoma (POAG) and ocular hypertension (OHT). Intraocular pressure (IOP) lowering effects in full responders are known to be 25–33% for this class; however, partial responders and nonresponders do exist. In clinical trials or prospective series, discontinuation and washout of PGAs is necessary to evaluate true change in IOP from novel surgeries and medical therapies. Clinical Relevance. To identify all relevant papers with pertinent data on washout of PGAs and quantify the duration and long-term effect of reported PGA washout periods in glaucoma and OHT patients. Methods. A systematic review and meta-analysis was conducted to investigate the long-term effects on IOP after discontinuation of topical PGAs POAG and OHT patients. The main search was conducted in MEDLINE/PubMed, EMBASE, Cochrane Library, CINAHL, Web of Science, and BIOSIS Previews and conference proceedings. Results. 1055 papers were identified, 548 were independently screened by two physicians., and 56 papers were analyzed for washout durations. The mean washout was found to be 4.56 weeks (±1.25), with the mode and median being 5 weeks. Five studies were analyzed as randomized control trials in which latanoprost was discontinued for 4 weeks prior to restarting another intraocular pressure-lowering drug. Meta-analysis revealed a 4-week discontinuation of latanoprost, on average, subjects returned to their baseline IOP. Conclusion. A significant IOP-lowering effect of latanoprost was not observed beyond 4 weeks, suggesting this may be an appropriate washout period for latanoprost. We could not identify appropriate washout periods for either travoprost or bimatoprost, although a majority of articles had 4-week washout durations for the two drugs. Despite the widespread use of this class of medication, there is a paucity of literature on the effects of PGA washout in patients that are treatment naïve to other topical medications.